Demographic Influences on Consumer Perceptions of Celebrity Endorsements in the Soft Drink Industry - Patel, Himalay; Chauhan, Rahul; Kalariya, Kush; Soni, Parth; Patel, Mohit (Journal of Advances in Accounting, Economics, and Management, 2024)
The study investigates the influence of demographic factors on consumer perceptions of celebrity endorsements in the soft drink industry. Utilizing ANOVA analyses, the research examines the impact of age, gender, and occupation on consumption patterns, brand preferences, and attitudes towards celebrity endorsements. Findings indicate a significant association between age and soft drink consumption frequency, with younger demographics showing higher consumption rates. However, gender and occupation do not significantly affect brand selection or endorsement perceptions. Notably, consumers across diverse demographics exhibit similar levels of susceptibility to celebrity endorsements, suggesting a universal appeal transcending gender and occupation. Despite demographic variations in consumption habits, celebrity endorsements wield comparable influence across consumer segments. The abstract underscores the importance of celebrity endorsements in shaping consumer behaviour within the soft drink industry and highlights the need for tailored marketing strategies targeting specific age groups.